2021
DOI: 10.1111/1471-0528.16663
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injury after episiotomy in vacuum extraction: an epidemiological study using an emulated randomised trial approach

Abstract: Objective: To emulate a randomized controlled trial investigating if lateral or mediolateral episiotomy compared to no episiotomy reduces the prevalence of obstetric anal sphincter injury (OASIS) in nulliparous women delivered with vacuum extraction. Design: A population-based observational study. Setting: Sweden. Population: 63 654 nulliparous women delivered with vacuum extraction derived from the Swedish Medical Birth Register 2000-2011, with a live singleton baby without known malformations in cephalic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 32 publications
1
28
0
2
Order By: Relevance
“…A reduction in the episiotomy rate in unassisted vaginal deliveries led to an increase in second-degree injuries of anatomic damage less than or equal to that caused by episiotomy without and increased rate of severe second-degree injuries 28 . There is continuing support for the use of episiotomy in vacuum delivery in nulliparas 29 although the number needed to treat was 27, and the results from randomized controlled trials to validate these recommendations are awaited 30 . Episiotomy is an obstetric technique associated with levator injury 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the episiotomy rate in unassisted vaginal deliveries led to an increase in second-degree injuries of anatomic damage less than or equal to that caused by episiotomy without and increased rate of severe second-degree injuries 28 . There is continuing support for the use of episiotomy in vacuum delivery in nulliparas 29 although the number needed to treat was 27, and the results from randomized controlled trials to validate these recommendations are awaited 30 . Episiotomy is an obstetric technique associated with levator injury 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although data from the literature show that episiotomy can reduce the prevalence of severe lacerations in assisted deliveries, the number of procedures needed to prevent one OASIS case is high [55]. Moreover, the group of patients who could benefit from episiotomy has not been identified yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study was underpowered to prove a significant change in the OA-SIS risk, mainly due to a high rate of episiotomy (52%) in the selective use group [53,54]. Ankarcrona et al [55] evaluated 63654 nulliparous women delivered with vacuum extraction. They showed that episiotomy could reduce the prevalence of OASIS from 15.5% to 11.8%.…”
Section: Intrapartum Factorsmentioning
confidence: 99%
“…We thank Drs Boujenah, Beddock and Harvey for their interest in our article ‘Obstetric anal sphincter injury after episiotomy in vacuum extraction: an epidemiological study using an emulated randomised trial approach’ 1,2 …”
Section: Disclosure Of Interestsmentioning
confidence: 99%